Decrease of Spermatogonia, Spermatocytes and Sertoli Cell Counts Male Mice (Mus musculus) Induced by Ethylene Glycol - Latief, Nuraini (Universitas Syiah Kuala, 2008)
The experiment was conducted to study the effect of ethylene glycol (EG) on disturbance of spermatogenesis process of the male mice. Sixteen mice at the age of 2 months were randomly into 4 groups of 4 each. The mice of control group were only given drinking water without EG. Group KPI, KP2, and KP3 were given EG 5, 10, and 15 ml/liter drinking water, respectively. On day 31 of post treatment, all mice were killed for their testis. The testis were collected and processed for microscopic examination and haematoxylin-eosin staining. The result showed that EG given orally for 30 days on male mice have negative effect on the process of spermatogenesis as the numbers of spermatogonia, spermatocyte and Sertoli cells decreased significantly (P0.01)